MICROBIAL GUT FLORA OF A FRESHWATER FISH GARRA MULLYA (SYKES) FROM MUTHA RIVER, NORTHERN WESTERN GHATS, INDIA - Rudresh, B. S.; Dahanukar, N.; Watve, G. M.; Renukaswamy, N. S. (Ecoprint: An International Journal of Ecology, 2011)
Preliminary exploration of gut flora of Garra mullya (Sykes) revealed nineteen bacterial strains showing wide diversity of enzyme production, morphological and biochemical characteristics. The factors which govern the diversity assessed through principal component analysis and correspondence analysis show that isolated strain have adaptation to utilization of variety resources like citrate and sugar, and also show tolerance to variety of environmental conditions like pH, salt, and bile in in-vitro condition. Key words: Gut flora; Bacterial diversity; Garra mullya DOI: 10.3126/eco.v17i0.4106 Ecoprint An International Journal of Ecology Vol. 17, 2010 Page: 53-57 Uploaded date: 29 December, 2010